Diminishing marginal utility: the respectable case for discounting?. (12th May 2004) - Price, Colin
Diminishing marginal utility is a potentially reasonable basis for discounting increasing future consumption per head. However, it applies to a different extent to those whose income growth prospects differ, to different growth scenarios, and to products whose output is differently constrained by natural resource and technological limitations. Diminishing marginal utility is irrelevant to non-marginal consumption and to the totality of consumption. It may even, perversely, lead to some non-marginal values increasing through time. As for that means of increasing consumption − reinvestment of revenues − it is constrained by circumstances and in practice does not happen to the extent required to justify customary discount rates. The simplifying assumption of a uniform discount rate depends on possibilities for trading that actually do not exist.